Effect of forage crop establishment on dissolved organic carbon dynamics and leaching in a hill country soil - Chibuike, Grace; Burkitt, Lucy; Camps‐Arbestain, Marta; Bishop, Peter; Bretherton, Mike; Singh, Ranvir (Soil use and management, 2019)
Intensive agricultural activities could affect the dynamics and leaching of dissolved organic carbon (DOC) and nitrate from agricultural soils to receiving waters. This study investigated soil DOC dynamics immediately (0–12 days) after spraying a hill country perennial pasture with agrochemicals to establish a winter forage crop for supplementary feed production. Two treatments were examined—perennial pasture (without agrochemicals) and swede (Brassica napobrassica Mill.) cropping (after spraying with agrochemicals), both growing on a Typic Eutrudept. Soil samples were collected from various depths down to 1 m, before the application of agrochemicals (day 0) and 1, 6 and 12 days thereafter. Dissolved organic carbon concentration below the surface soil (<5 cm) was generally not altered by the agrochemicals. This was further proved by the isotopic monitoring of DOC leaching on this soil. Conversely, the agrochemicals significantly (p = 0.03) increased DOC concentration within the 0–5‐cm soil depth on day 1, due to the direct contribution of organic molecules and/or displacement of organic compounds at adsorption sites by the agrochemicals; and on day 6, due to root necromass decomposition. The increase of nitrate in soil solution at this depth (0–5 cm) on days 6 and 12 suggests that the agrochemicals may have also enhanced nitrogen (N) mineralization in the surface soil. However, the significantly (p = 0.04) higher DOC/nitrate (molar ratio) of the agrochemical treatment suggests that the agrochemicals used for clearing out pasture before forage crop establishment could lead to a short‐term increase in surface soil denitrification.